Cu2ZnSnS4 Electrodeposition by Sulfurization of Metallic Precursors. (25th October 2017) - Perelstein, Gonzalo; Valdes, Matias; Vazquez, Marcela
Abstract : This work describes the electrodeposition of a Cu-Zn-Sn precursor on conducting glass that transforms into Cu2 ZnSnS4 during a heat treatment at 500 °C in vaporized sulfur. Citrate and hydroxyl concentrations were adjusted to fix the pH value in 5.9, so that Cu2 ZnSnS4 could be deposited on top of ZnO in solar cells built in superstrate configuration. The deposits were characterized by X-ray diffraction, Raman spectroscopy, scanning electronic microscopy, UV-Vis spectroscopy and photoelectrochemical techniques. Cu2 ZnSnS4 films obtained with short electrodeposition times are good-quality, p-type absorbers suitable to be used in kesterite thin films solar cells. The most promising results were obtained using 0.1 mol L -1 sodium citrate, which is attributed to a higher Zn content in the precursor deposit.